1991
DOI: 10.1537/ase1911.99.33
|View full text |Cite
|
Sign up to set email alerts
|

Genealogical position of native Taiwanese(Bunun Tribe) in East Asian populations based on tooth crown morphology.

Abstract: The 17 tooth crown traits of the Bunun, one of the aboriginal tribes in Taiwan, were observed and classified, and their frequencies were compared with Sinodonts and Sundadonts defined and classified in East Asian populations by , in order to estimate the genealogical position of the Bunun tribe in East Asia. In the respective comparisons of the 17 traits, the Bunun have considerable resemblance to Sinodonts on shoveling (UI1), double shoveling (UIl) and deflecting wrinkle (LM 1), while on tuberculum dentale (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Some arguments against the theory have been highlighted, particularly in the recent studies by Dodo (1992), Doi et al (1997), Doi (1998Doi ( , 2003Doi ( , 2004, Dodo et al (1998Dodo et al ( , 2000, and Asato and Doi (1999). From the viewpoint of dental morphology, Manabe et al (1999a) performed a study using dental plaster casts of modern, young, living Okinawa main islanders; their study suggested that this population was much more similar to the migrant Yayoi and modern Japanese main island populations than to the Jomonese and Hokkaido Ainu populations. Subsequently, some evidence that the modern Nansei islanders show a greater affinity to the migrant rather than to the native Japanese was additionally provided by Manabe et al (1999bManabe et al ( , 2001Manabe et al ( , 2003a.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some arguments against the theory have been highlighted, particularly in the recent studies by Dodo (1992), Doi et al (1997), Doi (1998Doi ( , 2003Doi ( , 2004, Dodo et al (1998Dodo et al ( , 2000, and Asato and Doi (1999). From the viewpoint of dental morphology, Manabe et al (1999a) performed a study using dental plaster casts of modern, young, living Okinawa main islanders; their study suggested that this population was much more similar to the migrant Yayoi and modern Japanese main island populations than to the Jomonese and Hokkaido Ainu populations. Subsequently, some evidence that the modern Nansei islanders show a greater affinity to the migrant rather than to the native Japanese was additionally provided by Manabe et al (1999bManabe et al ( , 2001Manabe et al ( , 2003a.…”
Section: Discussionmentioning
confidence: 99%
“…The eight significant traits on the first axis, namely UI1 shoveling, UI1 double shovel, UM1 cusp 5, LM2 Y-groove, LM1 cusp 6, LM2 4-cusp, LM1 deflecting wrinkle, and LM1 protostylid, are predominantly the traits that have shown obvious differences between sinodonty and sundadonty in previous analy- Table 1. ses (Turner, 1987(Turner, , 1990Manabe et al, 1991. The first axis can be used to distinguish the populations exhibiting sinodonty from those exhibiting sundadonty.…”
Section: Interpretation Of the Axesmentioning
confidence: 99%
See 3 more Smart Citations